TAGGING GENDER, MISSING THE MARK: A CRITICAL LOOK AT LITERACY CLOUD’S GENDER-THEMED STORIES - Latumeten, Anna Anganita Theresia; Janah, Ulum (Faculty of Letters Universitas Balikpapan, 2025)
Room to Read’s online reading platform, Literacy Cloud, positions itself as a digital literacy resource committed to promoting inclusive and gender-equal learning for children. This study examines how gender equality is represented in stories tagged under the “Gender Equality” category on the platform. Employing a descriptive qualitative approach, the study analyzes all 19 stories listed under this tag, with particular attention to thematic content related to gender representation. The findings reveal notable inconsistencies between the platform’s stated mission and its content categorization practices. Of the 19 stories examined, only six meaningfully promote gender-equal values in ways that are accessible to children. Eleven stories contain no identifiable gender-related themes, while one story reinforces traditional gender roles despite being classified as a gender-equality text. These results point to a critical issue of misclassification rather than content scarcity, suggesting that current tagging practices may obscure—rather than facilitate—access to genuinely gender-inclusive narratives. The study underscores the importance of accurate curation and rigorous editorial oversight in digital literacy plat-forms that seek to advance gender equality.